Effects of mode of presentation on ratings of empathic communication in medical interviews - Nicolai, Jennifer; Demmel, Ralf; Farsch, Karin (Patient education and counseling, 2010)
Objective - To test the impact of nonverbal behaviour on the assessment of a clinician's level of empathic communication. - Methods - One hundred volunteers were asked to assess a clinician's level of empathic communication using the Rating Scales for the Assessment of Empathic Communication in Medical Interviews (REM). Participants were randomly assigned to three groups differing with regard to the level of nonverbal information made available to them. Participants either watched a simulated medical interview, listened to an audio-only version of this interview, or read a transcribed version of the interview. - Results - Compared to watching a video and listening to an audiotape, respectively, reading a transcribed version of the interview produced lower empathy ratings and interrater reliabilities. - Conclusions - The findings suggest that assessments of a clinician's level of empathic communication may differ according to the level of nonverbal information made available to the raters. - Practice implications - Focusing on the verbal level of communication alone ignores the fact that empathy can be expressed through nonverbal means. Hence, nonverbal channels need to be taken into account in addition to the verbal channel when conducting research on empathic communication in health care.